2008
DOI: 10.1001/archgenpsychiatry.2007.18
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of Bipolar Spectrum Conditions in the Comorbidity of Mood and Substance Use Disorders

Abstract: In comparison with major depression, bipolar II disorder was associated with the development of alcohol and benzodiazepine use and disorders. There was less specificity of manic symptoms that tended to predict all levels of the substances investigated herein. The different patterns of association between mood disorders and substance use trajectories have important implications for prevention and provide lacking information about underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
102
3
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 168 publications
(124 citation statements)
references
References 58 publications
(83 reference statements)
14
102
3
5
Order By: Relevance
“…However, the overall figures for abstinence and drinks per drinking day suggest that the groups can be treated together in a dual diagnosis programme and that benefits continue after discharge. There is recent evidence for differences between depression and bipolar disorder based upon the characteristics of the depressive episodes (Mitchell et al, 2011) as well as obvious syndromal characteristics (DSM-IV), but many reports emphasize the similarities between the two disorders (Akiskal et al, 1995;Angst et al, 2010;Smith et al, 2011), particularly in situations of co-morbidity with substance use disorders (Merikangas et al, 2008) suggesting the possibility of a spectrum disorder (Smith et al, 2008). Overall, this study suggests that their psychoeducational and addiction treatments may be undertaken together successfully.…”
Section: Discussionmentioning
confidence: 69%
“…However, the overall figures for abstinence and drinks per drinking day suggest that the groups can be treated together in a dual diagnosis programme and that benefits continue after discharge. There is recent evidence for differences between depression and bipolar disorder based upon the characteristics of the depressive episodes (Mitchell et al, 2011) as well as obvious syndromal characteristics (DSM-IV), but many reports emphasize the similarities between the two disorders (Akiskal et al, 1995;Angst et al, 2010;Smith et al, 2011), particularly in situations of co-morbidity with substance use disorders (Merikangas et al, 2008) suggesting the possibility of a spectrum disorder (Smith et al, 2008). Overall, this study suggests that their psychoeducational and addiction treatments may be undertaken together successfully.…”
Section: Discussionmentioning
confidence: 69%
“…Similar to prior high risk studies of BPD, we found an elevated risk of SUD, particularly alcohol use disorders, among offspring of probands with BPD, but not MDD. The prospective data demonstrating an increased risk of alcohol dependence among community adults with BPD (Merikangas et al, 2008) highlight the potential benefit of prevention of alcohol dependence through intervention in youth with early manifestations of BPD. The other non-affective disorder associated with parental BPD was childhood SAD, replicating the findings of an earlier prospective community study of youth (Bruckl et al, 2007) which found a 7-fold increased risk of BPD among youth with earlier SAD.…”
Section: Discussionmentioning
confidence: 99%
“…This implicates a link between mood disorders and substance abuse or dependence disorders and a genetic link between alcoholism and bipolar disorder has been suggested (Brady and Lydiard, 1992;Sonne and Brady, 2002;Merikangas and Gelemter, 1990;Merikangas et al, 2008). Individuals with manic symptoms may be at greater risk for the later onset of alcohol and cannabis dependence.…”
Section: A Link Between Mood Disorders and Substance Abusementioning
confidence: 91%